A comunidade disciplinar de Química no Brasil – 1971/1986 - Rodrigues, Nicole Pinotte [UNIFESP] (2020)
The period from 1971 to 1986 was marked, in Brazil, by years of military regime, redemocratization process, various instabilities, transformations, rise and decline of groups and ideas and everything else that accompanies these processes. In Education, particularly in Science teaching, it was a time of investment in the importation and translation of North American projects, emergence of opposition or complementation ideas to these, development of graduate courses and research in Education, precariousness of high schools, due to the increased demand, and the promulgation of Lei nº 5.692/71. In the scope of the History of the School Subjects, it was made, in this work, an investigation on the school subject of Chemistry in the above-mentioned period, considering some of the contributions of the disciplinary community organized at the end of the 1970’s, in São Paulo state. This community was formed by school teachers, professors, undergraduate and graduate students, researchers and Education Secretary employees. For this investigation, the document analysis methodology was used in the records of the I ENEQ (1982), in a Project for improving Chemistry teaching developed by one of the first groups of Chemistry teaching research, GEPEQ (1984), in the curriculum proposals for secondary school Chemistry teaching of years 1978 and 1986, as well as other publications. For enriching the research, four members of this first generation of the disciplinary community were interviewed: one, who has been a professor since the beginning of the movement, one professor who was a high school teacher at the start of the community organization, one professor who was part of the pedagogical Chemistry Team of the Education Secretary and one high school Chemistry teacher, who has been working in it since 1974, and participates actively in the various actions of the community since its beginning. It was possible to identify several spheres of the community’s operation: textbooks, teaching projects, academic papers, official documents, initial and continuing Chemistry teachers training. Among the main aspects of the practices and purposes of the community for the Chemistry subject are: experimentation, cognitivist approaches, Science History, daily life, critical spirit formation.